(untitled) (Research, Society and Development, 2019)
This article discusses the understanding and participation of a group of teachers of the Early Years related to the Common National Curriculum Base (BNCC), during the course of its course. This is a qualitative research that is developed through a case study, whose subjects are 17 teachers of the 4th and 5th grade of elementary school in a city in the interior of Rio Grande do Sul. The data were produced through a questionnaire. semi-structured categorized according to the principles of Bardin’s Content Analysis (2009) and the theoretical contribution of Libêneo (2010, 2011), Aguiar and Dourado (2018), in addition to the BNCC itself (Brazil, 2017) and other legislations. Through data analysis were organized: the first refers to the profile of teachers; The second emphasizes the participation and studies carried out during the process of building the BNCC. the third highlights, from the teacher’s point of view, elements of information about the BNCC; and the fourth, shows the teachers’ knowledge about the Natural Sciences section. Most teachers participated in the public consultation process and expressed information consistent with the disclosure of the BNCC. However, there is a need to broaden and deepen such knowledge, regarding the effective content of the theoretical and methodological foundation of the BNCC and specifically the area of Natural Sciences.